Implementation of Digital-Based Al-Quran Reading and Writing Training Methods for Children in Pangkalan Village, Losarang District, Indramayu Regency - Carsinih; Tita Rizqiyah (Konsultan Jurnal Ilmiah Indonesia, 2024)
The Qur'an is the word of Allah revealed to the Prophet Muhammad SAW. through the intermediary of the Angel Gabriel. As the people of the Prophet Muhammad SAW, we should practice and understand the importance of learning to read and write the Qur'an from an early age. One of the benefits of learning to read and write the Qur'an itself is that it can be a guide for those who read and practice it. Learning the Qur'an is not only in the Mosque or Prayer Room, etc. However, learning the Qur'an can be done only with gadgets, here the function of digitalization applies, especially in this sophisticated era. The method of implementing this socialization is by means of counseling and interactive face-to-face methods at TPQ Darul Istiqomah. The results of this socialization activity show that